Reduction of Non-Specific Protein Adsorption Using Poly(ethylene) Glycol (PEG) Modified Polyacrylate Hydrogels In Immunoassays for Staphylococcal Enterotoxin B Detection - Paul T. Charles; Veronte R. Stubbs; Carissa M. Soto; Chris R. Taitt; Brett D. Martin; Brandy J. White (Sensors, 2009)
Three PEG molecules (PEG-methacrylate, -diacrylate and -dimethacrylate) were incorporated into galactose-based polyacrylate hydrogels and their relative abilities to reduce non-specific protein adsorption in immunoassays were determined. Highly crosslinked hydrogels containing amine-terminated functionalities were formed and used to covalently attach antibodies specific for staphylococcal enterotoxin B (SEB). Patterned arrays of immobilized antibodies in the PEG-modified hydrogels were created with a PDMS template containing micro-channels for use in sandwich immunoassays to detect SEB. Different concentrations of the toxin were applied to the hydrogel arrays, followed with a Cy3-labeled tracer antibody specific for the two toxins. Fluorescence laser scanning confocal microscopy of the tracer molecules provided both qualitative and quantitative measurements on the detection sensitivity and the reduction in non-specific binding as a result of PEG incorporation. Results showed the PEG-modified hydrogel significantly reduced non-specific protein binding with a detection limit for SEB of 1 ng/mL. Fluorescence signals showed a 10-fold decrease in the non-specific binding and a 6-fold increase in specific binding of SEB.